2020
DOI: 10.3390/ijerph17197030
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Alcohol Policies on Suicidal Behavior: A Systematic Literature Review

Abstract: Alcohol consumption has been found to be related to suicidal behavior at the individual and population level, but there is lack of literature reviews on the effect of alcohol policies on suicidal behavior. Therefore, the aim of the current study is to conduct a systematic literature review of the impact of alcohol policies at the population level on suicidal behavior and ideation. We searched the Cochrane CENTRAL, Cochrane DARE, EMBASE, Medline, ProQuest, PsycINFO, PubMed, SCOPUS, and Web of Science electronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 53 publications
0
23
0
Order By: Relevance
“…Our findings are consistent with other data showing alcohol regulations are associated with falls in suicide. 29 Therefore (re)-implementation of laws and regulations, such as taxation, and sales restrictions on certain hours or days may be a cost-effective public health policy to reduce suicide as well as other alcohol-related mortality. 30 …”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with other data showing alcohol regulations are associated with falls in suicide. 29 Therefore (re)-implementation of laws and regulations, such as taxation, and sales restrictions on certain hours or days may be a cost-effective public health policy to reduce suicide as well as other alcohol-related mortality. 30 …”
Section: Discussionmentioning
confidence: 99%
“…The young people in this study spoke about the accessibility and normalisation of alcohol use and the impact that this has on their suicidal ideation and attempts. A recent systematic review of international literature [ 29 ] found that by changing policies related to accessibility and cost of alcohol there was a decrease in suicide rates. The results highlight the importance of including assessment and formulation of alcohol and substance use when working with young people with suicidal ideation.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond these possibilities, the evidence underscores the need for government to strengthen the enforcement of the country's alcohol policy to prevent access and sale of alcoholic beverages to underage persons (Ministry of Health Ghana, 2016). A recent systematic review suggests that strengthening policies targeted at reducing harmful alcohol consumption could contribute to reducing suicidal behaviours (Kõlves et al, 2020).…”
Section: Factors Associated With Suicidal Ideationmentioning
confidence: 99%